2019
DOI: 10.21608/ejchem.2019.16475.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dunaliella salina extract alleviates the toxic impact of Dioxin induced endocrine disruption in Nile tilapia

Abstract: OLLUTION of lakes and seas in Egypt become a severe problem as it produces a lot of wastes and toxic chemicals. The water pollution induces a lot of endocrine disruptions in aquatic organisms. Several endocrine organs are influencing by pollution such as testes, ovaries, pituitary, hypothalamus, thyroid, and adrenal organs. Propositions of upsetting endocrine chemicals (EDCs) can meddle with fish larval advancement affecting the delicate balance of the biological ecosystem. Endocrine disruption effects on repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Extraction of Dunaliella salina D. salina was cultivated, harvested, and methanolic extracted at National Research Centre (NRC), according to Bassem, Abd El Tawab [7].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extraction of Dunaliella salina D. salina was cultivated, harvested, and methanolic extracted at National Research Centre (NRC), according to Bassem, Abd El Tawab [7].…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated gene expression changes in Hsp90, Cyp1a1 and MT in livers treated with dioxin only and Dunaliella salina plus dioxin Figure (5)(6)(7). Hsp90 levels were determined by real-time PCR.…”
Section: Effect Of Dioxin On the Induction Of Stress-related Genesmentioning
confidence: 99%
“…It was also reported that [8], low chlorinated-PCBs have anti-androgenic and estrogenic effects by inhibition of AhR signaling and moderate CAR/PXRmediated activities. A toxicity of dioxin-like PCBs to endocrine was also reported [9,10]. Therefore, the production of PCBs was completely prohibited in the 1970s.…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, D. salina was reported to have antibacterial and antiviral activities [ 41 ], antioxidant and anti-inflammatory properties [ 35 ], enhance immune response [ 45 ], have a neuroprotective effect [ 46 , 47 ], and genoprotective activity [ 48 ]. Furthermore, D. salina is used in sun-protection products to protect skin from ultraviolet sun rays [ 40 ].…”
Section: Introductionmentioning
confidence: 99%